An efficient synthesis of dinaphthothiophene derivatives - Karoon Sadorn (2018)
A short and efficient synthesis of dinaphthothiophene and its derivatives was achieved by employing oxidative photocyclization of the corresponding dinaphthyl sulfides as a key step. © 2008 Elsevier Ltd. All rights reserved.